0% found this document useful (0 votes)
305 views

Derivative of Algebraic Function

The document discusses differentiation formulas for algebraic functions. It provides formulas for finding the derivatives of constants, powers of x, products of functions, quotients of functions, composite functions, and implicit functions. It also covers finding higher order derivatives. Some key points covered include: - The derivative of a constant is 0. The derivative of a power of x is the power times x to the power minus one. - The derivative of a product of functions is the sum of each function multiplied by the derivative of the other. - The derivative of a composite function is the derivative of the inner function times the derivative of the outer function. - Higher derivatives can be found by continuing to take derivatives of previous

Uploaded by

reyi
Copyright
© © All Rights Reserved
Available Formats
Download as PPTX, PDF, TXT or read online on Scribd
0% found this document useful (0 votes)
305 views

Derivative of Algebraic Function

The document discusses differentiation formulas for algebraic functions. It provides formulas for finding the derivatives of constants, powers of x, products of functions, quotients of functions, composite functions, and implicit functions. It also covers finding higher order derivatives. Some key points covered include: - The derivative of a constant is 0. The derivative of a power of x is the power times x to the power minus one. - The derivative of a product of functions is the sum of each function multiplied by the derivative of the other. - The derivative of a composite function is the derivative of the inner function times the derivative of the outer function. - Higher derivatives can be found by continuing to take derivatives of previous

Uploaded by

reyi
Copyright
© © All Rights Reserved
Available Formats
Download as PPTX, PDF, TXT or read online on Scribd
You are on page 1/ 43

Derivative of Algebraic

Function
Differentiation Formulas for Algebraic Function
•  (c)=0 where c is any constant
• ()= where n is any real number
• ()=
•=
• )=
•=
•= The Chain Rule
 (c)=0 where c is any constant
• The derivative of any constant is equal to zero

Example

 (-3)=0
 (5)=0

()=0
(1/4)=0
 
()= where n is any real number
• The derivative of a power of x is equal to power times x raised to the power minus one

Example   3 1 3 2
𝑦= √ 𝑥 + 3 𝑦
 

√𝑥 2
 
=𝑥
3 3 3 2
 
()=5
 
()=
 
√ 𝑦 =√𝑥
  3 2
3 3
  𝑦 =𝑥
  2
()= ()= - 3
 𝑑𝑦 3
= 𝑥2 +
−2
𝑥
1 −5
3
𝑦= 𝑥 −1
𝑑𝑥 2 3   2 3
𝑦′= 𝑥
3
  3√𝑥 −2 𝟐
𝑦′= + 3 5  𝑦′=
2 3√𝑥 𝟏
𝟑
𝟑 𝒙
()=
 
• The derivative of the power of a function is equal to the power times the function raised to
the power minus one multiply by the derivative of a function

 EXAMPLES

 =2

()=(10x+3)

(=(3) =
=
 
• The derivative of product of two functions is equal to the first function times the derivative of
second function plus second function times the derivative of the first function

 EXAMPLE
     

 
(2x)

 ¿ 𝟓 𝒙 𝟒 − 𝟔 𝒙𝟐 −𝟐𝟒
 
)=
• The derivative of quotient of two functions is equal to the denominator times the derivative of the
numerator minus the numerator times the derivative of denominator, all over the square of the
denominator
 EXAMPLE
•     

 
=
 
=
 
=
=
 
• The derivative of a composite function of f and g is equal to the product of their respective
derivative
 EXAMPLE
  𝑦=(𝑢 )2  𝑢=4 𝑥−3
   𝑑𝑦 𝑑𝑢
=2 ( 𝑢 ) =4
𝑑𝑢 𝑑𝑥
 
 
y’

y’

 
y’
 
=
• The derivative of a composite function of f and g is equal to the product of their respective derivative
 EXAMPLE

 
2
3 𝑥 −2  
    𝑦 =(𝑢 )
5 𝑢= 3
1−𝑥
  𝑑𝑦 =5 (𝑢 ) 𝑑𝑢
4 ( 1− 𝑥 3 ) ( 6 𝑥 ) − (3 𝑥2 − 2)(− 3 𝑥 2)
𝑑𝑢 𝑑𝑥
= 3 2
(1− 𝑥 )
 
4 4 2
6 𝑥 −6 𝑥 +9 𝑥 −6 𝑥
¿ 
  (1− 𝑥3 )2
4 2
  3 𝑥 −6 𝑥 + 6 𝑥
¿ 3 2
(1− 𝑥 )
 
 
 
=
• If variable x is a function of y then the derivative dy/dx is equal to the reciprocal of the given function y

 EXAMPLE
𝑥
     
𝑦=
√ 2

 
 Y’ =

 
Y’ =
Implicit Differentiation
of Algebraic Function
=  = 
• 
-=36 =(
 
 -=36
 = -36
 
=( =   =36+
 = -4
 =
 
=(  
=(2)
 =(  =(

 =(x)
 =((2)(
 = ( (
 =(x)
=   =((

 =  =(
 =

 =
Example 1 Example 3

• 
-=36  - =
 8x-=0  2(x+y)(1+y’)- 2(x-y)(1-y’)= y’
 = =
 2x+2xy’+2y+2yy’-2x+2xy’+2y-2yy’= y’
Example 2  4xy’+4y= y’

 -+ =0  xy’- y’ =
 y’(x- ) =
  𝑥2 − 5 𝑥 (2
12
′ 2 ′
𝑦 𝑦 ) + 𝑦 (− 5)+24 𝑦 𝑦 =0
 y’ =
 =0
 = -

 = -
𝟓 𝒚 𝟐 −  𝟏𝟐 𝒙 𝟐
 𝒚 ′ =  
𝟐𝟒 𝒚 − 𝟏𝟎 𝒙 𝒚
Higher Derivatives
Example 1

 -+3

 𝑦 ′ ′ =30 𝑥 −4
  𝒚 ′ ′ ′ =𝟑𝟎

Example 2

 ++3y+3 x = 

 +3y’+ 3y’+6xy+6xyy’+ 3=2+2y’

 +3+6xy-2)=- - 6xy- 3+2  3y = 3


 
𝑦 =− ¿ ¿  
3(3)


 
𝑦 ′=−

1
  𝑦 =0
Derivative of Trigonometric Function
Pythagorean Relations  
cos=
Reciprocal Relationships
•   =1
1.  
s=
 =1
2. =  s=
 
t= =1
3. 1+=
 
c= =1
 
c=

Double Number identities Half Number identities Tangent-Cotangent Relationships


   
 
1. cos2 =
=
= =
3. t =
Formulas of Differentiation of Trigonometric Functions
•  (sinu) = cosu (u)
• (cosu) = (u)
• (tanu) = (u)
• = (u)
• (secu) = s(u)
• (cscu) = (u)
 
(sinu) = cosu (u)   = (u)  (secu) = s(u)

)•      )
)tan)(3
y’ = 3 )tan)

 (cosu) = (u)

 )
 (cscu) = (u)

 +2x-1)
)c)(3 +2
 (tanu) = (u) y’ = (3 +2) )c)

 )
Example 1

•𝑦=𝑠𝑖𝑛𝑥+𝑐𝑜𝑠
  2𝑥
𝑦 ′=𝑐𝑜𝑠 𝑥 − 𝑠𝑖𝑛 2 𝑥 (2)
  Double Number identities Other Solution:
𝑠𝑖𝑛
  2 𝜃=2 𝑠𝑖𝑛𝜃 𝑐𝑜𝑠𝜃 4 4
𝑦′=𝑐𝑜𝑠 𝑥− 4 𝑠𝑖𝑛𝑥𝑐 𝑜𝑠𝑥
    𝑦=𝑐𝑜𝑠 𝑥 − 𝑠𝑖𝑛 𝑥
 ) )
  𝑦 ′=𝑐𝑜𝑠 𝑥 (1− 4 𝑠𝑖𝑛𝑥)   𝑦 = 𝑐𝑜𝑠 2 𝑥
Example 2   𝑦 ′ =− 𝑠𝑖𝑛 2 𝑥 (2 )
  𝑦=𝑐𝑜𝑠 4 𝑥 − 𝑠𝑖𝑛 4 𝑥  𝑦 ′=− 2 𝑠𝑖𝑛 2 𝑥
 𝑦 ′=(𝑐𝑜𝑠𝑥 ) 4 4
−(𝑠𝑖𝑛𝑥)
 𝑦′=4 ( 𝑐𝑜𝑠𝑥 )3 (− 𝑠𝑖𝑛𝑥)− 4 ( 𝑠𝑖𝑛𝑥 )3 (𝑐𝑜𝑠𝑥)
Pythagorean Relations
 𝑦 ′=− 4 𝑠𝑖𝑛𝑥𝑐𝑜𝑠𝑥 (𝑐𝑜𝑠 2 𝑥+𝑠𝑖𝑛 2 𝑥 )  =1 Product of the sum and Difference
Double Number identities of the same two terms
  𝑦 ′ =− 2(2 𝑠𝑖𝑛𝑥𝑐𝑜𝑠𝑥 )  𝑥
2
−  𝑦 2 =( 𝑥+ 𝑦 ) ( x − y )
𝑠𝑖𝑛
  2 𝜃=2 𝑠𝑖𝑛𝜃 𝑐𝑜𝑠 𝜃
 𝑦 ′=− 2 𝑠𝑖𝑛 2 𝑥   cos2 =
Example 3
  𝑠𝑖𝑛𝑥 𝑐𝑜𝑠 2 𝑥
•𝑦=
  ′
𝑦 =𝑠𝑖𝑛𝑥 ( 2𝑐𝑜𝑠𝑥 ) (−𝑠𝑖𝑛𝑥)+𝑐𝑜𝑠2 𝑥𝑐𝑜𝑠𝑥
  ′ 2
𝑦 =−2 𝑠𝑖𝑛 𝑥𝑐𝑜𝑠 𝑥+𝑐𝑜𝑠 𝑥 3

 𝑦 ′ =− 𝑐𝑜𝑠𝑥 ( 2 𝑠𝑖𝑛 2 𝑥− 𝑐𝑜𝑠2 𝑥 ) Pythagorean Relations


 
=1
  𝑦 ′ =− 𝑐𝑜𝑠𝑥 ¿
 

 𝑦 ′ =− 𝑐𝑜𝑠𝑥 (2− 3 𝑐𝑜𝑠2 𝑥)


Example 4
  𝑦= 𝑐𝑜𝑠2 2 𝑥
Double Number identities
 𝑦 ′=2(𝑐𝑜𝑠 2 𝑥)(− 𝑠𝑖𝑛 2 𝑥)(2) Recall:

  𝑦 =− 4 𝑠𝑖𝑛 2 𝑥𝑐𝑜𝑠 2 𝑥
 
 )

 )
Example 5

  𝑠𝑖𝑛𝑥 𝑐𝑜𝑠 2 𝑥
•𝑦=
  ′ 2
𝑦 =𝑠𝑖𝑛𝑥 ( 2𝑐𝑜𝑠𝑥 ) (−𝑠𝑖𝑛𝑥)+𝑐𝑜𝑠 𝑥𝑐𝑜𝑠𝑥
  ′
𝑦 =−2 𝑠𝑖𝑛2 𝑥𝑐𝑜𝑠 𝑥+𝑐𝑜𝑠 3 𝑥 Pythagorean Relations
 𝑦 ′ =− 𝑐𝑜𝑠𝑥 ( 2 𝑠𝑖𝑛 2 𝑥 − 𝑐𝑜𝑠2 𝑥 )
 
=1
  𝑦 ′ =− 𝑐𝑜𝑠𝑥 ¿
 

 𝑦 ′ =− 𝑐𝑜𝑠𝑥 (2− 3 𝑐𝑜𝑠2 𝑥)


Example 6
  𝑦= 𝑐𝑜𝑠2 2 𝑥
  𝑦 ′=2(𝑐𝑜𝑠 2 𝑥)(− 𝑠𝑖𝑛 2 𝑥)(2) Double Number identities

𝑦 ′ =−
Recall:
 
 )
4 𝑠𝑖𝑛2 𝑥𝑐𝑜𝑠 2 𝑥  

 )
Example 7
• 
′ 4
 
𝑦 = 𝑠𝑖𝑛 𝑥 ( 4 )¿ Double Number identities
  ′ 3 3 2
𝑦 =4𝑠𝑖𝑛 𝑥  𝑐𝑜𝑠 𝑥(−𝑠𝑖𝑛 𝑥+𝑐𝑜𝑠 𝑥) 2
  cos2 =
3
 𝑦 ′ = (2 𝑠𝑖𝑛𝑥𝑐𝑜𝑠 𝑥 ) 𝑐𝑜𝑠 2 𝑥  
2
3
 𝑦 ′ = ( 𝑠𝑖𝑛 2 𝑥 ) 𝑐𝑜𝑠 2 𝑥
2
3
  𝑦 ′ = 𝑠𝑖𝑛 2 𝑥𝑐𝑜 𝑠 2 𝑥
2

Other Solution  
   
  𝑠𝑖𝑛 4 2 𝑥
𝑦= 4
16   sin 2𝜃
 
𝑦=
3
4 𝑠𝑖𝑛 2 𝑥 𝑐𝑜𝑠 2 𝑥 (2)
′ ( 2
4
) =( 𝑠𝑖𝑛 𝜃 𝑐𝑜𝑠 𝜃  )
4

16   𝑠𝑖𝑛 2 𝜃 4 4
  ′ 3
𝑠𝑖𝑛 2 𝑥 𝑐𝑜𝑠 2 𝑥 = 𝑠𝑖𝑛 𝑥   𝑐𝑜𝑠 𝑥
16
𝑦=
2
Example 7
• 
′ 4
 
𝑦 = 𝑠𝑖𝑛 𝑥 ( 4 )¿ Double Number identities
  ′ 3 3 2
𝑦 =4𝑠𝑖𝑛 𝑥  𝑐𝑜𝑠 𝑥(−𝑠𝑖𝑛 𝑥+𝑐𝑜𝑠 𝑥) 2
  cos2 =
3
 𝑦 ′ = (2 𝑠𝑖𝑛𝑥𝑐𝑜𝑠 𝑥 ) 𝑐𝑜𝑠 2 𝑥  
2
3
 𝑦 ′ = ( 𝑠𝑖𝑛 2 𝑥 ) 𝑐𝑜𝑠 2 𝑥
2
3
  𝑦 ′ = 𝑠𝑖𝑛 2 𝑥𝑐𝑜 𝑠 2 𝑥
2

Other Solution  
   
  𝑠𝑖𝑛 4 2 𝑥
𝑦= 4
16   sin 2𝜃
 
𝑦=
3
4 𝑠𝑖𝑛 2 𝑥 𝑐𝑜𝑠 2 𝑥 (2)
′ ( 2
4
) =( 𝑠𝑖𝑛 𝜃 𝑐𝑜𝑠 𝜃  )
4

16   𝑠𝑖𝑛 2 𝜃 4 4
  ′ 3
𝑠𝑖𝑛 2 𝑥 𝑐𝑜𝑠 2 𝑥 = 𝑠𝑖𝑛 𝑥   𝑐𝑜𝑠 𝑥
16
𝑦=
2
Example 8
 𝑑 𝑦 = 𝑑𝑢 × 𝑑𝑢
•𝑦=
  1− 𝑐𝑜𝑠 4 𝑥 1 −𝑐𝑜𝑠 4 𝑥

 
𝑦 =𝑢
√ 1+𝑐𝑜𝑠 4 𝑥
1
2
 
𝑢=
𝑑𝑢
 
1+ 𝑐𝑜𝑠 4 𝑥 𝑑 𝑦
( 1+𝑐𝑜𝑠4 𝑥 ) ( 𝑠𝑖𝑛 4 𝑥 ) ( 4 ) −(1 −𝑐𝑜𝑠 4 𝑥)(− 𝑠𝑖𝑛 4 𝑥 )(4) 𝑑𝑥
𝑑𝑥

=
2

𝑑 𝑦

1
𝑑𝑥

1 − 𝑐𝑜𝑠 4 𝑥
×
8 𝑠𝑖𝑛 4 𝑥
( 1+ 𝑐𝑜𝑠 4 𝑥 ) 2
= 2
1 + 𝑐𝑜𝑠 4 𝑥

 𝑑𝑢 = 1 𝑢
−1
2 𝑑𝑥 ( 1+𝑐𝑜𝑠4 𝑥 )
𝑑𝑦 2   𝑑𝑢
=− 4 𝑠𝑖𝑛 4 𝑥 ¿ ¿ 𝑑 𝑦
  =
1
×
8 𝑠𝑖𝑛 4 𝑥

𝑑𝑥− 4 𝑠𝑖𝑛 4 𝑥 (− 2 )
𝑑𝑢
𝑑𝑥
2
√ 1 − 𝑐𝑜𝑠 4 𝑥
1 + 𝑐𝑜𝑠 4 𝑥
( 1+ 𝑐𝑜𝑠 4 𝑥 ) 2

 
𝜃 1 − 𝑐𝑜𝑠 𝜃 𝑠𝑖𝑛
𝑑𝑥𝜃
=


2
( 1+ 𝑐𝑜𝑠 4 𝑥 )
𝑡𝑎𝑛 =± =
2 1+𝑐𝑜𝑠𝑑𝑢𝜃 1+𝑐𝑜𝑠 𝜃 8 𝑠𝑖𝑛 4 𝑥 𝑑 𝑦
  =
4 𝑠𝑖𝑛 4 𝑥
  𝑑𝑥
𝑡𝑎𝑛
4 𝑥
( 1 +𝑐𝑜𝑠 4 𝑥 ) ( 1 + 𝑐𝑜𝑠 4 𝑥 )
cos2
  = = 2
𝑑𝑥 ( 1+ 𝑐𝑜𝑠 4 𝑥 ) 2
 =1
 𝑠𝑒𝑐 𝜃 = 1 Other Solution: 4 𝑡𝑎𝑛
4 𝑥
 
𝑑 𝑦
=
2

𝑐𝑜𝑠 𝜃 𝑑𝑥
𝑡𝑎𝑛
4 𝑥 (
2
1 + 𝑐𝑜𝑠 2 2 𝑥 − 𝑠𝑖𝑛 2 2 𝑥

 =tan2x

 𝑦 ′ = 𝑠𝑒𝑐 2 𝑥 (2)  =
  𝑦 ′ = 2 𝑠𝑒𝑐 2 𝑥
Example 9 = 

•𝑦=2
  𝑠𝑖𝑛𝑥𝑐𝑠𝑐 2 𝑥  (sinu) = cosu (u)
 
   (cscu) = (u)
 
=1
 
  𝑐𝑜𝑠 𝜃
 
𝑐𝑜𝑡 𝜃=
𝑠𝑖𝑛 𝜃
 
 
  cos2 =
  𝑠𝑖𝑛 𝜃
𝑡𝑎𝑛 𝜃=
  𝑐𝑜𝑠 𝜃
 
=1
  =
Implicit Differentiation
of Trigonometric Function
Example 1
2 2
 𝑦= tan ⁡( 𝑥 + 𝑦)  ( 𝑦 ) = ( tan ⁡( 𝑥 + 𝑦) )
•𝑦=
  tan ⁡( 𝑥 + 𝑦)
1  1 2
2 ′
 𝑦 ′ = 𝑠𝑒𝑐 ⁡( 𝑥+ 𝑦)(1+ 𝑦 )
=  𝑦 =𝑡𝑎𝑛 2 ( 𝑥 + 𝑦 )
𝑦 tan ⁡(𝑥 + 𝑦)
  1 2 1 2
2 2
  𝑦 ′ = 𝑠𝑒𝑐 ⁡( 𝑥+ 𝑦)+𝑠𝑒𝑐 ( 𝑥 + 𝑦)
𝑦
=⁡𝑦 ′
( ) (
tan ⁡( 𝑥+ 𝑦) )
′ 2
  𝑦 − 𝑠𝑒𝑐 ( 𝑥 + 𝑦 ) 𝑦 ′ = 𝑠𝑒𝑐(2  𝑦()−2𝑥+
=𝑐𝑜𝑡𝑦)
2
(𝑥 + 𝑦)

 𝑦 (1 − 𝑠𝑒𝑐 2 ( 𝑥+ 𝑦 ))=𝑠𝑒𝑐 2 ( 𝑥 + 𝑦)
𝑠𝑒𝑐 2 ⁡( 𝑥+ 𝑦 ) ′ 𝑡𝑎𝑛2 ( 𝑥 + 𝑦 ) + 1  𝑠𝑒𝑐 𝜃 = 1
  𝑦

= 𝑦 =  
𝑐𝑜𝑠 𝜃
2
1 − 𝑠𝑒𝑐
2
( 𝑥+ 𝑦) − 𝑡𝑎𝑛 ( 𝑥 + 𝑦 )

  𝑦

=
𝑐𝑜𝑠 ⁡
1
2
(𝑥 + 𝑦 )
′  𝑦 = 𝑦 +1
2
=− 1 − 𝑦
−2 = 
−𝑦
2
− 𝑡𝑎𝑛 ( 𝑥 + 𝑦 )

  𝑠𝑖𝑛 𝜃
𝑡𝑎𝑛 𝜃 =
𝑐𝑜𝑠 𝜃
 1 +  1 + =
  1
 1 +) 𝑡𝑎𝑛 𝜃 =
𝑐𝑜𝑡 𝜃
Example 2
2 2
 ( 𝑦 ) = ( tan ⁡( 𝑥𝑦 ) )
•𝑦=
  tan ⁡( 𝑥𝑦 )
2
 𝑦 ′ = 𝑠𝑒𝑐
2 ′
⁡( 𝑥𝑦 )( 𝑥 𝑦 + 𝑦 )
 𝑦 =𝑡𝑎𝑛 2 ( 𝑥𝑦 )

  𝑦 ′ =(𝑡𝑎𝑛 ¿ ¿ 2 𝑥𝑦 +1)( 𝑥 𝑦 ′ + 𝑦 )¿
 𝑦

=( 𝑦 ¿ ¿ 2 +1 )( 𝑥 𝑦 ′ + 𝑦 ) ¿ = 

  𝑦′= 𝑦2 𝑥 𝑦′+ 𝑦3 + 𝑥 𝑦′+ 𝑦


 +y
 +y
 +1)


 
𝑦 = 𝑦 ¿ ¿
Example 3
sin
•  ( 𝑥+ 𝑦 ) +sin ( 𝑥 − 𝑦 )=1 = 
 =1

2  𝑠𝑖𝑛𝑥𝑐𝑜𝑠𝑦 =1
 2 𝑠𝑖𝑛𝑥 ( − 𝑠𝑖𝑛𝑦 ) 𝑦 ′ +𝑐𝑜𝑠𝑦 ( 2 𝑐𝑜𝑠𝑥 )= 0
  −2 𝑐𝑜𝑠𝑦𝑐𝑜𝑠𝑥

𝑦=
−2 𝑠𝑖𝑛𝑥𝑠𝑖𝑛𝑦

 
𝑦 =𝑐𝑜 𝑡𝑥𝑐𝑜𝑡𝑦
Differentiation
of Inverse Trigonometric
Function
Formulas of Differentiation of Trigonometric Functions
•  (Arcsinu) = (u)
• (Arccosu) = (u)
• (Arctanu) = (u)
• = (u)
• (Arcsecu) = (u)
• (Arccscu) = (u)
Example 1.  (Arcsinu) =

• 
2
 𝑦 ′ = 𝑥 2 2
+ 𝐴𝑟𝑐𝑠𝑖𝑛 2 𝑥 (2 𝑥 )
√ 1 − ( 2 𝑥)
1
 𝑦 ′ =2 𝑥
(√ 1 −4 𝑥
2
+ 𝐴𝑟𝑐𝑠𝑖𝑛 2 𝑥
)
 Example 2. (Arccosu) =

 𝑦 ′ = − ( 𝑐𝑜𝑠𝑥 )
2  
=1
√ 1 − ( 𝑠𝑖𝑛𝑥 )
  𝑦 ′ = − ( 𝑐𝑜𝑠𝑥 )
√ 𝑐𝑜𝑠 2 𝑥
  = -1
 (Arctanu) =
Example 3.

•𝑦=  𝐴𝑟𝑐𝑡𝑎𝑛4 3 𝑥 5
  ( 15 𝑥 4 )
𝑦 ′ = 4 ( 𝐴𝑟𝑐𝑡𝑎𝑛 3 𝑥 5 )3
1+(3 𝑥5 )2
  ′ 60 𝑥 4 𝐴𝑟𝑐𝑡𝑎𝑛4 3 𝑥5
𝑦 = 10
1 +9 𝑥

 Example 4. = (u)

2
 
y=9 𝑥 − 𝐴𝑟𝑐𝑐𝑜𝑡 3 𝑥
 

3
 𝑦 ′ = 18 𝑥 +162 𝑥 +3
2
1+9 𝑥
 
 (Arcsecu) =  Example 6.
Example 5. (Arccscu) =

′ 3
• 
y = Arcsec (1 − 4 𝑥 )  y

= ( 𝐴𝑟𝑐𝑐𝑠𝑐 2 𝑥 )
3

12 𝑥 2
 𝑦 ′ = 3 3 2
(1 − 4 𝑥 ) √( 1 − 4 𝑥 ) −1  
 𝑦 =
′ 12 𝑥 2
(1 − 4 𝑥 3 ) √ 1 − 8 𝑥 3+ 16 𝑥 6 − 1

12 𝑥 2  
 𝑦 =

(1 − 4 𝑥 3 ) √ 16 𝑥 6 − 8 𝑥3
2
 𝑦 =
′ 12 𝑥
(1 − 4 𝑥 3 ) √ 4 𝑥2 ( 4 𝑥 4 − 2 𝑥)

 𝑦 ′ = 12 𝑥 2
(1 − 4 𝑥 3 )(2 𝑥 ) √ (4 𝑥 4 − 2 𝑥)

 𝑦 ′ = 12 𝑥 2
(1 − 4 𝑥 3 )(2 𝑥 ) √ (4 𝑥 4 − 2 𝑥)
6𝑥
 𝑦 ′ = 3 4
(1 − 4 𝑥 ) √ (4 𝑥 − 2 𝑥 )
Derivatives of
Exponential and
Logarithmic Functions
Properties of Exponential Function Properties of Logarithmic Function

= lnx

+ +
= =
= =

r r
Formulas of Differentiation of Trigonometric Functions
•  () = (u)
• () = (u)
• () =
• =
Illustrative Examples

 () = (u)  () =

 () =
 () =

  =
 () = (u)
  =
 () =
  =

You might also like